INTERPERSONAL COMMUNICATION ROLE FOR SELF-CONCEPT OF CHILDREN AND FAMILIES - Muhammad Thariq (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
This study intends to know "How can interpersonal communication build family resilience in the face of increasingly tough challenges"? To reveal the reality of the authors use qualitative methods. To get the data, the author uses three techniques of data collection that is observation, in-depth interview and documentation study. The results of this study found that interpersonal communication plays an important role in shaping family resilience and strengthen the functioning of families facing increasingly severe challenges. Interpersonal communication between parent and child through the giving of statements such as "Know your family and remember who you are", "we live not alone" and "remember neighbors, remember family" can form self concept or character of child and family in society as do parents to the children / family in Neighborhood 1 Pasar 6 Kelurahan Tanjungsari Kecamatan Medan Selayang, Medan City, North Sumatera Province. There are positive family relationships and actions built on the basis of conversation, conformity, dependency and distribution of powers derived from parents and children as in families in Neighborhood I Pasar 6 Tanjungsari Village, Kec. Medan Selayang, so as to build a warm and supportive relationship that is characterized by mutual respect and care for each other. With the capital of interpersonal communication, the family can function in building relationships between families and social relations in the form of arisan aged 20 years more. Finally, the family communication (old family) upholds family secrets and restrictions on taboo matters.